Ideal Leader According to Quran - Muhammad Bahriannor; Nur Hana; Rahima Raihan Sya’bana; Rida Wati; Sri Wahyuni; Shanty Komalasari; Ceria Hermina (International Conference on Psychology and Education (ICPE), 2023)
Leaders are people who act and are involved in change. Humans are creatures that will continue to experience the difference. The passage of time makes humans think every day. Becoming a leader seems to be an absolute thing that humans must pass. The Islamic religion has designed all the references that can guide humans to live life, that is, the Qur'an. All instructions are listed and neatly arranged, including how to become a leader and how to lead. This article will contain about the ideal leader according to the Qur'an, which will explicitly explain one of the verses related to the leader, which is QS Al-Maidah (5): 57. The ideal leader according to the Qur'an is very important to be talked over because topics related to being a leader will not stop being discussed. Humans will always experience regeneration where each generation will become a leader, even in the smallest scope, leading himself. This journal uses the literature study method, where the explanations and materials needed to complete the journal are contained in journals, books, or other sources.